New materials of iguanodontians (Dinosauria: Ornithopoda) from the Lower Cretaceous Khok Kruat Formation, Ubon Ratchathani, Thailand - Samathi, Adun; Suteethorn, Suravech (Zootaxa, 2022)
We describe iguanodontian post-cranial remains, including a cervical vertebra, two dorsal vertebrae, five caudal vertebrae, a metacarpal, right femur, tibia and fibula, and a small femur possibly from a juvenile of the same taxon. This is the first record of a juvenile iguanodontian co-occurring with an adult from Thailand. The material was recovered from the Lower Cretaceous Khok Kruat Formation of Khok Pha Suam, Ubon Ratchathani Province, north-eastern Thailand. It was reconstructed to belong to a non-hadrosauriform styracosternan. This study provides the first osteological description of iguanodontian post-cranial material in Thailand and its potential autapomorphic features. However, whether it belongs to a previously named taxon or represents a new one cannot be assessed yet and must await further discovery.